2001
DOI: 10.1111/j.1478-4408.2001.tb00333.x
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Remazol Black B dye and its simulated dyebath wastewater by advanced oxidation processes in heterogeneous and homogeneous media

Abstract: This study focused on the degradation of hydrolysed Remazol Black B (CI Reactive Black 5), a common diazo reactive dye, in aqueous solution. In the presence of various dye auxiliary chemicals a typical Remazol Black exhausted dyebath liquor simulated, which was then treated with homogeneous [ozonation with hydroxy ions, and Fe(II) or Fe(III) with hydrogen peroxide] and heterogeneous (titanium dioxide with UV‐A irradiation) advanced oxidation processes. Treatment performance of the investigated advanced oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 18 publications
3
24
0
1
Order By: Relevance
“…However, pseudo-first-order reaction kinetics was observed by Arslan and Balcioglu (2001) for the degradation of Remazol black B dye and its simulated dyebath wastewater. Balci et al (2009) also reported that the degradation of …”
Section: Resultsmentioning
confidence: 99%
“…However, pseudo-first-order reaction kinetics was observed by Arslan and Balcioglu (2001) for the degradation of Remazol black B dye and its simulated dyebath wastewater. Balci et al (2009) also reported that the degradation of …”
Section: Resultsmentioning
confidence: 99%
“…The result is the formation of perhydroxyl radicals which are significantly less reactive species than hydroxyl radicals and thus directly influence the efficiency of dye degradation [25]. According to the literature, typical values of Fenton reagent ratio are in the range between 1:5 and 1:25 [28,32]. The optimal operating parameters for RB49 degradation by Fenton process established on the basis of TOC measurements are Fe 2þ /H 2 O 2 ¼ 1:20, c(Fe 2þ ) ¼ 0.5 mM, pH 3, where maximal TOC removal of 72.1% was achieved (Fig.…”
Section: Fenton Process Fe 2þ /H 2 Omentioning
confidence: 99%
“…Their elimination from wastewater effluents is now the subject of considerable concern of environmental remediation and has attracted many researchers in recent years. Most textile dyes are photolytically stable and refractory towards chemical oxidation [1] and these characteristics render them resistant towards decomposition by conventional biochemical and physico-chemical methods. Generally, adsorption on activated carbon, coagulation by a chemical agent or reverse osmosis was applied to such effluents [2,3].…”
Section: Introductionmentioning
confidence: 99%